Research trends and hotspots of COVID-19 impact on sexual function: A bibliometric analysis based on Web of Science - Xiaodu Xie; Pan Lei; Lumiao Liu; Jian Hu; Peihe Liang (Frontiers Media S.A., 2022)
BackgroundThe outbreak of coronavirus disease 2019 (COVID-19) has brought indelible harms to the world and aroused great concern worldwide. This paper aims to analyze the impact of COVID-19 on sexual function using bibliometrics, and summarize research hotspots in this field.MethodsRelevant publications concerning the impact of COVID-19 on sexual function in the Web of Science collection database (WoSCC) between January 1, 2020 and March 12, 2022 were screened and analyzed by bibliometric analysis using the visualization software CiteSpace and VOSviewer.ResultsOf the 1,054 publications screened, the United States (US) contributed the most (398/37.8%), followed by the United Kingdom (UK) (119/11.3%). Among all institutions, the University of Toronto in Canada enjoyed the largest number of publications (30), and Johns Hopkins University in the US enjoyed the highest frequency of citation (235). The journal INTERNATIONAL JOURNAL OF ENVIRONMENTAL RESEARCH AND PUBLIC HEALTH published the largest number of studies in this field (31), and the most-cited journal was LANCET. "Chow, Eric," "Ong, Jason J," and "Stephenson, Rob" tied for first place in publications (8), and "Fish, Jessica N." enjoyed the highest number of citations (99). Burstness analysis of references and keywords showed that the developing research trends in this field mainly focused on "sexual transmission" and "angiotensin converting-enzyme 2 (ACE2)" during the COVID-19 pandemic.ConclusionThe impact of COVID-19 on sexual function remains an urgent concern at present, and the management of sexual health during the pandemic needs to be further improved. More frequent and deeper cooperation between countries and institutions is required in future. Meanwhile, searching for more evidence on whether COVID-19 can achieve sexual transmission and the pathophysiological mechanisms underlying the impact of COVID-19 on sexual function remains a focus of research in the coming years.